An office of ethics: meetings, roles, and moral enthusiasm in animal protection. (16th March 2017) - Reed, Adam
Abstract : This essay explores the relationship between meetings and organizational ethics in an animal protection charity in Scotland. Here, recent 'professionalization' has seen the late introduction of an 'ethics of office' and accompanying impersonalization of roles. A consequent struggle emerges over what the relationship should be between the core message of the organization, as an office of animal ethics, and the 'personal' principles or ethical commitment of individual staff members. All of this comes to a head when persons, and office‐holders, meet.